Therapeutics for the correction of deep bite with intrusion in the anterior sector. Literature review - Machado Campoverde, Andrea Natalí (2022)
Deep bite is a complex problem in Orthodontics, considering it a great challenge in its correction, so it is of great importance for professionals to have a better understanding of the effectiveness of the different treatments, in order to achieve optimal therapeutic results. in this pathology. Based on this, this article aims to review the literature regarding the different types of treatments for tooth intrusion in the anterior sector for Deep Bite correction. The search for articles pertinent to the topic was carried out from 2012 to 2022, where the digital scientific databases were: PubMed, Lilacs, Science Direct, Scopus, Scielo, Google Scholar, during the selection process 32 articles were found with the desired features. Concluding that the deep bite can be treated by various intrusion systems, most of them being effective, achieving an intrusion in the maxillary incisors, in this way the miniimplants provide a more efficient reduction of the deep bite showing better results since they have a less extrusion in the molars and greater intrusion of the incisors, also presenting proclination and loss of sagittal and vertical anchorage less than that found in the different intrusion systems. There was also some degree of root resorption during the intrusion phase, independent of the intrusion mechanics used.